Coincident angle-resolved state-selective photoelectron spectroscopy of acetylene molecules: a candidate system for time-resolved dynamics. (9th March 2021) - Mandal, S.; Gopal, R.; Srinivas, H.; D'Elia, A.; Sen, A.; Sen, S.; Richter, R.; Coreno, M.; Bapat, B.; Mudrich, M.; Sharma, V.; Krishnan, S. R.
Abstract : We focus on detailed investigations of the molecular acetylene-vinylidene system in the photon energy range 19–40 eV where extreme-ultraviolet pulses can probe the dynamics effectively. Abstract : The acetylene-vinylidene system serves as a benchmark for investigations of ultrafast dynamical processes where the coupling of the electronic and nuclear degrees of freedom provides a fertile playground to explore the femto- and sub-femto-second physics with coherent extreme-ultraviolet (EUV) photon sources both on the table-top as well as free-electron lasers. We focus on detailed investigations of this molecular system in the photon energy range 19–40 eV where EUV pulses can probe the dynamics effectively. We employ photoelectron–photoion coincidence (PEPICO) spectroscopy to uncover hitherto unrevealed aspects of this system. In this work, the role of excited states of the C2 H2 + cation, the primary photoion, is specifically addressed. From photoelectron energy spectra and angular distributions, the nature of the dissociation and isomerization channels is discerned. Exploiting the 4π-collection geometry of the velocity map imaging spectrometer, we not only probe pathways where the efficiency of photoionization is inherently high but also perform PEPICO spectroscopy on relatively weak channels.